Microbiological profile of organisms causing bloodstream infections between 2004 and 2016 in a tertiary hospital Limpopo province South Africa - Girdler-Brown, Brendan V. (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.